Groundwater Recharge and Hydrogeochemical Evolution in Leizhou Peninsula, China. (19th August 2015) - Lu, Yintao; Tang, Changyuan; Chen, Jianyao; Chen, Junhong
Abstract : An analysis of the stable isotopes and the major ions in the surface water and groundwater in the Leizhou Peninsula was performed to identify the sources and recharge mechanisms of the groundwater. In this study, 70 water samples were collected from rivers, a lake, and pumping wells. The surface water was considered to have a lower salinity than the groundwater in the region of study. The regression equations for δ D and δ 18 O for the surface water and the groundwater are similar to those for precipitation, indicating meteoric origins. The δ D and δ 18 O levels in the groundwater ranged from −60‰ ; to −25‰ ; and −8.6‰ ; to −2.5‰, respectively, and were lower than the stable isotope levels from the winter and spring precipitation. The groundwater in the southern area was classified as the Ca 2+ -Mg 2+ -H C O 3 - -type, whereas the groundwater in the northern area included three types (Na + -Cl − -type, Ca 2+ -Mg 2+ -H C O 3 - -type, and Ca 2+ -Mg 2+ -Cl − -type), indicating rapid and frequent water-rock exchange in the region. A reasonable conclusion is that the groundwater chemistry is dominated by rock weathering and rainwater of local origin, which are influenced by seawater carried by the Asian monsoon.